Diagnostic Instrument Test of Renewable Energy Topics: Analysis of Conceptual Change Students Using the Rasch Approach - Ahmad Zulkarnain Zain; Achmad Samsudin; Lilik Hasanah (CV FOUNDAE, 2025)
The learning of students about abstract physics concepts faces multiple hurdles, which can result in misconceptions. Considering this problem, the present research intends to analyze students' misconception changes through a diagnostic tool based on the issue of renewable energy using the Rasch analysis methods. The Renewable Energy Topic Diagnostic Instrument (DITRET) was created with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The subjects of the study were 30 high school students aged 17 years (9 boys and 21 girls). DITRET has 20 components with four hierarchical stages for each item. During the analysis stage, students’ responses are classified into categories, and conceptual scores are then computed in the Rasch framework. The results showed that DITRET has strong reliability and validity in estimating students’ understanding of renewable energy. With some minor adjustments, this instrument can identify students’ conceptual changes and diagnose misconceptions on other physics topics. The research findings enhance the available literature, providing valid and reliable tools to measure, detect, and resolve misconceptions in the concept of renewable energy